Concordância entre as dosagens de sódio, potássio, cálcio e albumina na urina de 12 horas noturna e na primeira urina da manhã em participantes do Estudo Longitudinal de Saúde do Adulto (ELSA Brasil) - Leones Jose Tolentino (2018)
Introduction and objective: Dosage of urine analytes in which excretion does not remain constant throughout the day is often performed on timed (12hs or 24 hs) urine samples. However, in addition of being time consuming, it also presents a low rate of adhesion, contributing to errors in collection varying from 9 to 88%. The random sample has become a more reproducible option and a feasible alternative to collecting the timed urine sample. The aim of this study was to evaluate the agreement between sodium (Na), potassium (K), calcium (Ca) and albumin dosages in the urine of 12h at night and first morning urine in participants of the Longitudinal Study of Adult Health (ELSA-Brazil). Methods: A total of 137 volunteers were instructed to collect urine during the 12h of night and the first sample in the following morning. The samples were delivered to the laboratory team who validated the collection process. The samples were analyzed at the Clinical Pathology Laboratory Unit of the Hospital das Clínicas, Federal University of Minas Gerais / Ebserh, by Vitros 5600 Ortho Clinical Diagnostics Integrated System (Raritan, New Jersey). The agreement between the dosages was evaluated by the Lins coefficient, the Pearsons r and the Bland-Altman agreement method. To evaluate the influence of collection time and the first morning urine stasis, the groups were subdivided according to the collection time and the urinary stasis time. Results: Albumin dosage and albumin to creatinine ratio (ACR) showed the best coefficient and limit of agreement between samples of 12h nocturne and first morning urine in those samples collected between 06:30 a.m. to 08:15 a.m and with urinary stasis over 2 to 4h. The 12h samples showed the best coefficient and limits of agreement for calcium, potassium and sodium dosages in relation to the first morning urine samples with over 8 hours of urinary stasis. Conclusions: Based on the results of this study, the first morning urine albumin dosage and ACR should be performed preferably in a sample collected between 06:30 a.m. to 08:00 a.m. and with stasis between over 2 to 4 hours. The Ca, K and Na dosage presented satisfactory correlation and agreement between the 12h nocturnal samples with the first morning urine with urinary stasis over to 8 hs. These results maycontribute to a better standardization of these dosages in random samples.